Protection of earth observation satellites from radio-frequency interference: policies and practices [perspectives] - Luis Pedro; Manuel Sa; Rui Fernandes; Flavio Jorge; Mendonça, S. (IEEE Geoscience and Remote Sensing Magazine, 2022)
Carrying onboard remote sensing systems, Earth observation (EO) satellites provide unique global, systematic, and consistent space-based measurements of natural and man-made phenomena. Measurements can be produced on atmospheric, surface, and subsurface characteristics, properties, and constituents as well as other indicators and related data, enabling comparisons in time and across different parts of the globe, including remote and otherwise inaccessible areas.